Diversity of small molecule HIV‐1 latency reversing agents identified in low‐ and high‐throughput small molecule screens. Issue 3 (13th October 2019) - Hashemi, Pargol; Sadowski, Ivan
Abstract: The latency phenomenon produced by human immunodeficiency virus (HIV‐1) prevents viral clearance by current therapies, and consequently development of a cure for HIV‐1 disease represents a formidable challenge. Research over the past decade has resulted in identification of small molecules that are capable of exposing HIV‐1 latent reservoirs, by reactivation of viral transcription, which is intended to render these infected cells sensitive to elimination by immune defense recognition or apoptosis. Molecules with this capability, known as latency‐reversing agents (LRAs) could lead to realization of proposed HIV‐1 cure strategies collectively termed "shock and kill, " which are intended to eliminate the latently infected population by forced reactivation of virus replication in combination with additional interventions that enhance killing by the immune system or virus‐mediated apoptosis. Here, we review efforts to discover novel LRAs via low‐ and high‐throughput small molecule screens, and summarize characteristics and biochemical properties of chemical structures with this activity. We expect this analysis will provide insight toward further research into optimized designs for new classes of more potent LRAs.